The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/1096-9926(200101)63:1<3::aid-tera1001>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Screening for fetal alcohol syndrome in primary schools: A feasibility study

Abstract: Background This project was undertaken as a feasibility study to determine the possibility of screening for fetal alcohol syndrome (FAS) in early school‐age children for epidemiological and interventional purposes. Methods All elementary schools in two counties in Washington State were asked to screen first graders for possible FAS. A child was screen positive if found to be growth deficient, to have certain specific facial abnormalities, or have a known history of substantial alcohol exposure in gestation. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 8 publications
2
40
0
1
Order By: Relevance
“…The active case ascertainment method has been employed in epidemiological studies of FASD conducted in the USA [11] and a number of other countries, including South Africa [32], Italy [38], and Croatia [39]. Unlike the surveillance method described above, the active case ascertainment approach has targeted all potential participants in a given population.…”
Section: The Active Case Ascertainment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active case ascertainment method has been employed in epidemiological studies of FASD conducted in the USA [11] and a number of other countries, including South Africa [32], Italy [38], and Croatia [39]. Unlike the surveillance method described above, the active case ascertainment approach has targeted all potential participants in a given population.…”
Section: The Active Case Ascertainment Methodsmentioning
confidence: 99%
“…It has been estimated that the proportion of children on the spectrum without dysmorphia may be three times as high as that of FAS [18]. This method may also underestimate the rates of FAS because FAS and other genetic disorders are not often diagnosed at birth [11,25]. Furthermore, most health centers may not have clinicians to diagnose fetal alcohol syndrome.…”
Section: Surveillance Of Fetal Alcohol Syndromementioning
confidence: 99%
“…El alcohol o sus derivados acetilaldehídos interfieren en los procesos metabólicos necesarios para el desarrollo del encéfalo durante la embriogénesis. Ocurre entre el 30 y el 50 de las madres que consumen alcohol durante el embarazo 6 . Condiciones perinatales como las distocias del parto, el parto pretérmino, fetos menores de 32 semanas y peso menor de 1.500 g, y la hipoxia neonatal pueden producir daño cerebral y provocar DI.…”
unclassified
“…Clarren, Randels, Sanderson, and Fineman (2001) studied the feasibility of screening for FASD in primary schools for epidemiological and interventional purposes.…”
Section: Diagnosis and Screening For Fasdmentioning
confidence: 99%
“…Most families noted improvements in terms of access to services or accommodations. Clarren et al (2001) identified several distinct advantages to screening at this point in a child's school career: his or her age allows for an accurate diagnosis; school entry was the first time after the newborn period that students come into contact with a single system; early academic interventions are possible, and are believed to reduce secondary disabilities; and children with another previously unrecognized syndrome might also be identified and offered appropriate services. Watson et al (2007) later observed that many problems related to FASD are not apparent in infancy, but can appear at an older age.…”
Section: Diagnosis and Screening For Fasdmentioning
confidence: 99%